THE ROLE OF PARENTS IN INCREASING THE ENTHUSIASM FOR LEARNING OF CLASS IV STUDENTS - Sulistyowati, Kintoko Aldi Saputra; Abduh, Muhammad (AULADUNA: Jurnal Pendidikan Dasar Islam, 2023)
Abstract The learning process is important in achieving success in education. One of the learning process elements that influences learning achievement is family support, especially parents. This research aims to describe the role of parents in increasing students’ enthusiasm for learning in class IV of SD Negeri 1 Simo. The method used was analytical descriptive with a qualitative approach. Data collection techniques in this research were observation and interviews. Observation was conducted at SD Negeri 1 Simo, especially for 34 students of class IV. Interviews were carried out with three sources, namely students, teachers, and parents, based on several indicators of enthusiasm for learning. The research results indicated that the role of parents influences students’ enthusiasm for learning. Their efforts to increase students’ enthusiasm can make it easier for them to learn, such as providing adequate learning facilities, giving rewards to their children, maintaining harmonious conditions at home, and giving encouragement and advice. The implications of these findings can be used as a reference for parents in educating their children to improve achievements at school.